2019
DOI: 10.1007/s12325-019-00957-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Community Pharmacist-Delivered Information Program on the Follow-up of Type-2 Diabetic Patients: A Cluster Randomized Controlled Study

Abstract: IntroductionLow-quality communication between patients and care providers and limited patient knowledge of the disease and the therapy are important factors associated with poor glycemic control in patients with type 2 diabetes. We conducted a multicenter study to determine whether structured and tailored information delivered by pharmacists to type 2 diabetic patients could improve patient treatment adherence, hemoglobin A1c (HbA1c) levels and knowledge about diabetes.MethodsOne hundred seventy-four pharmacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
0
28
0
2
Order By: Relevance
“…It was reported that patients in the pharmacist intervention group showed greater improvement in their ability of self-management and knowledge of diabetes after 6 months of patient education when compared with those in the control group. 11 According to a meta-analysis including 43 randomized controlled trials conducted in foreign countries, including Asian countries and the United States of America, intervention by pharmacists who provided pharmaceutical care in addition to diabetes education helped in significantly reducing the A1c level when compared with that aided by usual medical instruction given by the medical team to patients with type 2 diabetes. 12 It was also shown that pharmacist-led interventions in the community have contributed to improved adherence and better disease control.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that patients in the pharmacist intervention group showed greater improvement in their ability of self-management and knowledge of diabetes after 6 months of patient education when compared with those in the control group. 11 According to a meta-analysis including 43 randomized controlled trials conducted in foreign countries, including Asian countries and the United States of America, intervention by pharmacists who provided pharmaceutical care in addition to diabetes education helped in significantly reducing the A1c level when compared with that aided by usual medical instruction given by the medical team to patients with type 2 diabetes. 12 It was also shown that pharmacist-led interventions in the community have contributed to improved adherence and better disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the strengths of different healthcare professionals seems to increase the effect of the intervention compared to that of the pharmacist alone (van Eikenhorst et al, 2017). However, support programs for diabetic patients focused on patients' specific needs through tailored intervention during individual sessions seem to be more effective in achieving improvement of biological parameters (HbA1c) and patient selfmanagement (Jameson and Baty, 2010;Harrington and Noar, 2012;Michiels et al, 2019).…”
Section: Strengths Of the Diab-vh Programmentioning
confidence: 99%
“…General advice related to lifestyle measures and the proper use of medication are provided by the prescriber when issuing the prescription and by the community pharmacist when dispensing medicines. Pharmacists have thus always been able to play a role in the improvement of clinical outcomes, health status and lifestyle factors in patients known for failing to reach the clinical and biological goals assigned by their diabetologists (ie, body mass index (BMI) and glycated hemoglobin (HbA1c) respectively) (Jameson & Baty, 2010;van Eikenhorst et al, 2017;Yaghoubi et al, 2017;Aguiar et al, 2018;Bukhsh, Khan, et al, 2018;Deters et al, 2018;Iqbal et al, 2019;Michiels et al, 2019;Syarifuddin et al, 2019;Abdulrhim et al, 2020;Nogueira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…An example of this is in the management of type 2 diabetes [ 10 ]. For example, one study found that, for patients with type 2 diabetes, pharmacist delivered care significantly improved their ability to self-manage their condition, as seen by decreased glycosylated hemoglobin (HbA1c) clinical values 6 months post intervention [ 11 ]. Research also shows that through MTM counseling on lifestyle modifications (e.g., physical activity, nutrition), disease state management, and medication adherence, pharmacists make an important contribution to the diabetes care team [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous work has demonstrated the economic, clinical, and humanistic benefits of pharmacist delivered MTM services [ 8 , 9 , 10 , 11 ], an enhanced, condition specific MTM program for patients with type 2 diabetes mellitus (T2DM) has not yet been evaluated in the literature. A pilot, condition specific, pharmacist delivered MTM program was therefore implemented by a national MTM provider to empower self-management of tT2DM, optimize medication regimens, address gaps in care continuity, improve glycemic control, reduce risks of diabetes-related complications, and improve chronic condition management for patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%